how do you solve -9+8k=7+4k

Guide :

how do you solve -9+8k=7+4k

how do you solve it and check solution,  

Research, Knowledge and Information :


How do you solve -9 + 8k = 7 + 4k? + Example - Socratic.org


Now back to the original problem. 8k - 4k = 7 + 9? Now just subtract/add the like terms together! 4k = 16 This is the tricky part; ... How do you solve #-9 + 8k = 7 ...
Read More At : socratic.org...

Can you help me solve -9+8k=7+4k - OpenStudy


Can you help me solve -9+8k=7+4kk=4. first you would subtract the 4k from the right side so that you can get the k on only one side of ... Can you help me solve -9+8k ...
Read More At : openstudy.com...

How do you solve 2-3/4k=1/8k+9? | Socratic


How do you solve #2-3/4k=1/8k+9#? Algebra Linear Equations Multi-Step Equations with Like Terms. 1 Answer ... How do you solve #3x + 5- 6( x + 1) = 4x + 5#?
Read More At : socratic.org...

Can you help me solve -9+8k=7+4k - OpenStudy


... Can you help me solve -9+8k=7+4kPut all the terms with the same variables on one side. . ... Can you help me solve -9+8k=7+4k. Algebra
Read More At : openstudy.com...

Home | MIT - Solve


If you have a solution to one of these big global challenges, ... Become part of Solve’s global community and enjoy these member benefits: Access to Solve events;
Read More At : solve.mit.edu...

what is the answer to 8k-4(k-1)+7-k - Brainly.com


what is the answer to 8k-4(k-1)+7-k ... rules this means you have to solve your ... teh parenthesis this gives you 8k-4k+1+7-k now you have to ...
Read More At : brainly.com...

Solve for k. 3/4k+3/8k=1/2 by the way 3/4,3/8, and1/2are ...


Solve for k. 3/4k+3/8k=1/2 by the way 3/4,3/8, and1/2are fractions 1. Ask for details ; Follow; ... You can specify conditions of storing and accessing cookies in ...
Read More At : brainly.com...

Suggested Questions And Answer :


How do I solve y=-x-4

How do I solve y=-x-4 I need to be able to plot these points on a graph but i don't know how to solve the problem.   make an x & y axis. ( like a cross one line goes vertical an the other horizontal) put equal dimention for x & y line From center line moving
Read More: ...

how to solve for x with fractions

Simplifying x3 + 3x2 + -4x = 0 Reorder the terms: -4x + 3x2 + x3 = 0 Solving -4x + 3x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-4 + 3x + x2) = 0 Factor a trinomial. x((-4 + -1x)(1 + -1x)) = 0 Subproblem 1 Set the factor 'x' equal to zero an
Read More: ...

How do you solve this problem? solve for d: n= m+3d/4

Problem: How do you solve this problem? solve for d: n= m+3d/4 I need help solving this and seeing how it was solved since I am having trouble figuring out what to do and how to solve it thanks. n = m + 3d/4 n - m = (m + 3d/4) - m n - m = 3d/4 4(n - m) = (3d/4)4 4(n - m) = 3d 4(n - m)/3 = 3
Read More: ...

Solve, using linear combination. 3x + y = 4 2x + y = 5

line 1: 3x+y=4    or y=4-3x line 2: 2x+y=5 line 1 -line2...(3x-2x)+(y-y)=4-5 or x=-1 y=4-3x=4+3=7
Read More: ...

how can i solve these equations?

how can i solve these equations? x + 3y – z = 2 x – 2y + 3z = 7 x + 2y – 5z = –21 We eliminate one of the unknowns (x, y or z, take your choice), leaving two unknowns. Then, we eliminate a second one, giving us an equation with only one of the unknowns. Solve for that and plug that value in
Read More: ...

Inequalities

9x+6=51 9x=51-6 9x=45 x=5
Read More: ...

how do you solve 3/x+5

how do you solve 3/x+5 I'm confused on how to solve this problem All you have is an expression. There is nothing to solve until you make it an equation. 3/x + 5 = -8 3/x + 5 = 14 3/x + 5 = 0 3/x + 5 = 38.67 3/x + 5 = -91 3/x + 5 = 43 Those can be solved, because they are complete. Each one will h
Read More: ...

x - z = -3, y + z = 9, -2x + 3y +5z = 33

Problem: x - z = -3, y + z = 9, -2x + 3y +5z = 33 1) x - z = -3 2) y + z = 9 3) -2x + 3y + 5z = 33 Add equation 2 to equation 1.      x     - z = -3 +(    y + z =  9) ------------------   x + y     = 6 4)
Read More: ...

how to solve by substitution

how to solve by substitution .3x+3y=1.2(100) "Substitution" implies there are TWO equations in two unknowns. You solve one of them for one of the unknowns in terms of the other, e.g., solve for y in terms of x. THEN, you substitute that value into the other equation where the y is, and yo
Read More: ...

2x+y=9 x-2z=-3 2y+3z=15

2x+y=9 x-2z=-3 2y+3z=15 Forgot how to do This. Problems Solving systems of this type requires eliminating all but one unknown so you can solve for that unknown. Then, plug that value into one of the equations to solve for another of the unknowns. Finally, plug both of those values into an equation
Read More: ...

Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question
  • Start your question with What, Why, How, When, etc. and end with a "?"
  • Be clear and specific
  • Use proper spelling and grammar
all rights reserved to the respective owners || www.painphr.com || Terms of Use || Contact || Privacy Policy
Load time: 0.1187 seconds